Implikasi Ajaran Yoga Bagi Pamangku di Bali dalam Aspek Tri Sarira - Nerta, I Wayan (Jayapangus Press, 2023)
The Patanjali Sutra Yoga teachings are not only gestures but also give the mandate to the existence of body and mind. A priest at the time of nganteb upakara was likened to a